UM REDESCOBRIMENTO HISTORIOGRÁFICO DO BRASIL (Revista de História Regional, 2007)
This article handles the renovation on the Brazilian historiography produced by the works of Gilberto Freyre, Sérgio Buarque de Holanda and Caio Prado Jr., and discusses comparatively the most important characteristics of the interpretative lines of History followed by such authors, accentuating the relation between their perspectives and the historic context of the 1930s in Brazil.